Writing against the Wall: Academic Writing as a Subjectivity Instrument - Baquero M, Pedro; Martínez, Jorge (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper addresses the academic writing as an oversight mechanism regarding technic and scientific discourse. Additionally, it analyzes defining features of scientific papers on the point of its dominance in academic publications and its function as a subjectivity instrument among university professors and re- searchers. From the antinomy of writing opening/closing in an analytic logic, it discusses the creation’s patterns, production and distribution of the academic papers in current conditions when facing knowle- dge commodification. Furthermore, it shows how the academic guidelines policies generate writing’s suppression and submissiveness. This analysis presents the academic paper as a “closed” and dystopic way of writing in humanities, that seems to contradict its heuristic and creative function when building and interpreting social matters. Finally, it attracts humanities writers and researchers’ attention to defend and relay, from the writing itself, in alternative ways to resist an extreme instrumentalization of writing